2008
DOI: 10.1124/dmd.108.023895
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Protein 2-Mediated Estradiol-17β-d-glucuronide Transport Potentiation: In Vitro-in Vivo Correlation and Species Specificity

Abstract: ABSTRACT:Multidrug resistance protein 2 (MRP2) is a multispecific organic anion transporter expressed at important pharmacological barriers, including the canalicular membrane of hepatocytes. At this location it is involved in the elimination of both endogenous and exogenous waste products, mostly as conjugates, to the bile. Estradiol-17␤-D-glucuronide (E 2 17␤G), a widely studied endogenous substrate of MRP2, was shown earlier to recognize two binding sites of the transporter in vesicular transport assays. MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
(49 reference statements)
1
21
2
Order By: Relevance
“…These results are in agreement with previous reports proposing that MRP2 contains two interacting binding sites (Bodo et al, 2003;Zelcer et al, 2003). Results similar to our data were reported by Zelcer et al (2003) and Herédi-Szabó et al (2009), who had K 0.5 values of 120 and 150 M, respectively, for E 2 17␤G transport in MRP2 membrane vesicles prepared from baculovirus-infected Sf9 cells. The K m value for transport of NMQ in our P-gp vesicles was 2.9 M, which is lower than the K m value of 14.7 M reported for the transport of this substrate into membrane vesicles prepared from P-gp-overexpressing Sf21 insect cells (Hooiveld et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with previous reports proposing that MRP2 contains two interacting binding sites (Bodo et al, 2003;Zelcer et al, 2003). Results similar to our data were reported by Zelcer et al (2003) and Herédi-Szabó et al (2009), who had K 0.5 values of 120 and 150 M, respectively, for E 2 17␤G transport in MRP2 membrane vesicles prepared from baculovirus-infected Sf9 cells. The K m value for transport of NMQ in our P-gp vesicles was 2.9 M, which is lower than the K m value of 14.7 M reported for the transport of this substrate into membrane vesicles prepared from P-gp-overexpressing Sf21 insect cells (Hooiveld et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…The functional uptake activity in vesicles prepared from the transiently transfected cells was higher than that of vesicles prepared from stably transfected cells. In our hands, the level of activity in these vesicles as indicated by V max values (picomoles per minute per milligram of protein) for probe substrates used in this study is even higher than that reported for MRP2 (Zelcer et al, 2003;Telbisz et al, 2007;Pedersen et al, 2008;Herédi-Szabó et al, 2009), BCRP (Pál et al, 2007, Xia et al, 2007, and P-gp (Hooiveld et al, 2002) vesicles prepared from Sf9 cells. The transient transfection approach and large-scale production technologies described in this study should be generally applicable for other ABC efflux transporters of interest, e.g., MRP3, MRP4, and bile salt export pump.…”
Section: Discussioncontrasting
confidence: 40%
“…Moreover, CDF could be transported by Mrp1 and Mrp3, which suggests that the assay may also recognize the activities of enzymes other than Mrp2 [22]. Therefore, the specific activity of influx and efflux transporters must be investigated using various labeled or unlabeled compounds specific for each transporter: e.g., estradiol-17␤-glucuronide is specific for the uptake transporter OATP8 and the efflux transporter Mrp2 [23], and taurocholate is a specific substrate of the uptake transporters NTCP and OATP and the efflux transporter BSEP [24].…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that potentiated MRP2/Mrp2-mediated E 2 17bG transport in in vitro models exerted the same effect in vivo. Even the concentration dependence of the effect was similar in the three systems (VT, sandwich cultured hepatocytes, and biliary excretion in rats) [13].…”
mentioning
confidence: 96%
“…The latter system has the advantage of endogenous expression levels, but lacks specificity, as multiple transporters are expressed in the CMV. Using the MRP2 VT assay, Pedersen et al [8] have screened 191 structurally diverse compounds to find a significant number of unambiguous stimulators (13) and borderline stimulators (17) of the E 2 17bG transport.…”
mentioning
confidence: 99%